The Influence of Emotional Intelligence and Work Environment on Job Satisfaction and Its Implications for the Performance of Healthcare Workers at Robert Wolter Mongisidi General Hospital - Rinal Pardomuan Purba; Mochamad Vrans Romi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This study aims to determine the effect of: emotional intelligence of health workers on job satisfaction at Tk.II Robert Wolter Mongisidi Hospital, work environment with job satisfaction of health workers at Tk.II Robert Wolter Mongisidi Hospital, emotional intelligence of health workers with performance at Tk.II Hospital. Robert Wolter Mongisidi, working environment with the performance of health workers at Tk.II Robert Wolter Mongisidi Hospital. job satisfaction of health workers with performance at Tk.II Robert Wolter Mongisidi Hospital. The population in this study were all health workers at Tk.II Robert Wolter Mongisidi Hospital as many as 203 people. Sampling in this study was carried out by random sampling technique using the formula Slovin as many as 67 people. The data collection method used a questionnaire. The validity and reliability tests were then carried out. The data analysis techniques used were descriptive analysis, multiple linear regression, hypothesis testing, and coefficient of determination. The results showed that: There is an influence of the emotional intelligence of health workers with job satisfaction at Tk.II Robert Wolter Mongisidi Hospital, There is an influence of the work environment with job satisfaction of health workers at Tk.II Robert Wolter Mongisidi Hospital, There is an influence of the relationship of emotional intelligence of health workers with performance at Tk.II Robert Wolter Mongisidi Hospital, There is an influence of work environment on the performance of health workers at Tk.II Robert Wolter Mongisidi Hospital, There is an effect of job satisfaction of health workers with performance at Tk.II Robert Wolter Mongisidi Hospital.